Different activities of the conserved lysine residues in the double-stranded RNA binding domains of RNA helicase A in vitro and in the cell - Xing, Li; Niu, Meijuan; Zhao, Xia; Kleiman, Lawrence (Biochimica et biophysica acta, 2014)
RNA helicase A regulates a variety of RNA metabolism processes including HIV-1 replication and contains two double-stranded RNA binding domains (dsRBD1 and dsRBD2) at the N-terminus. Each dsRBD contains two invariant lysine residues critical for the binding of isolated dsRBDs to RNA. However, the role of these conserved lysine residues was not tested in the context of enzymatically active full-length RNA helicase A either in vitro or in the cells. The conserved lysine residues in each or both of dsRBDs were substituted by alanine in the context of full-length RNA helicase A. The mutant RNA helicase A was purified from mammalian cells. The effects of these mutations were assessed either in vitro upon RNA binding and unwinding or in the cell during HIV-1 production upon RNA helicase A–RNA interaction and RNA helicase A-stimulated viral RNA processes. Unexpectedly, the substitution of the lysine residues by alanine in either or both of dsRBDs does not prevent purified full-length RNA helicase A from binding and unwinding duplex RNA in vitro. However, these mutations efficiently inhibit RNA helicase A-stimulated HIV-1 RNA metabolism including the accumulation of viral mRNA and tRNALys3 annealing to viral RNA. Furthermore, these mutations do not prevent RNA helicase A from binding to HIV-1 RNA in vitro as well, but dramatically reduce RNA helicase A–HIV-1 RNA interaction in the cells. The conserved lysine residues of dsRBDs play critical roles in the promotion of HIV-1 production by RNA helicase A. The conserved lysine residues of dsRBDs are key to the interaction of RNA helicase A with substrate RNA in the cell, but not in vitro.